Evaluation of pH - Dependent Release of Doxorubicin from Hydroxyapatite-Sodium alginate Composites - ONOYIMA , C. C.; NWOYE , E. E. (Nigerian Journal of Pharmaceutical and Applied Science Research, 2020)
Cancer is one of the diseases where pH-sensitive delivery system is highly desirable because of the more acidic environment of tumour cells compared to normal cells. The effect of the pH of the release medium (pH 3, pH 5 and pH 7.4) on the release profile of hydroxyapatite-sodium alginate (HASA)-loaded doxorubicin, an anticancer drug, was studied. In situ preparation of hydroxyapatite-sodium alginate nanocomposite (HASA) was carried out by the wet chemical precipitation method. Drug loading and in-vitro drug release study was carried out using synthetic body fluid as the release medium. Doxorubicin (DOX) release rate was initially faster at acidic conditions than at physiologic condition. The cumulative percent release of DOX after five hours was 30.53% in pH 3.0, 33.64% in pH 5.0 and 18.21% in pH 7.4. After 33 hours, 38.56% of DOX has been released in pH 3.0, 36.42% in pH 5.0, and 55.43% in pH 7.4 There was preferential release of doxorubicin from the composite at acidic condition which indicates that the composite is a potential carrier for targeted release of DOX to cancer cells.